Filter dan Kps Untuk Meningkatan Pemahaman Materi dan Hasil Belajar Sejarah Pada Materi Manusia Praaksara - Purwatiningsih (IJoIS: Indonesian Journal of Islamic Studies, 2021)
Many students consider history learning in the form of rote learning, so students are reluctant to learn, especially for students who do not like to read. Teachers have an important role in presenting learning so that the lessons presented are not boring. Therefore, skills are needed in developing interesting approaches and methods or learning models that make students enthusiastic to follow the teaching and learning process to completion. The use of learning media can be used to enhance the effectiveness and efficiency in achieving learning objectives. Documentary films and History Smart Cards are one of the media that can be used to improve understanding of the material and student learning outcomes on the material of human life. The method used in this paper is a qualitative method so that the resulting data is in the form of descriptive data, where the data will provide an overview of the use of media-based historical learning models (Media Based Learning. The use of filters and KPS has an influence on increasing understanding and learning outcomes on the material). Pre-literate human life that can be seen from the completeness of learning outcomes used for cognitive assessment and filling in the KPS can be used as a psychomotor dimension.